Strategies to Improve Employee Perfomance through Work Dicipline and Position Promotion in order to Improve Services at PT. PLN (Persero) ULP Karang in the Customer Service Section - Shelli Monicha; M. Oktaviannur (Cita konsultindo, 2024)
The purpose of this study is to outline the approach used by PT PLN (Persero) Karang Customer Service Unit to enhance services by promoting and enforcing work discipline among employees. This kind of research is qualitative, descriptive, and involves three informants in total: managers, supervisors, and workers. Three approaches are utilized to acquire data: documentation, observation, and interviews. The results of this research show that work discipline can help maintain order and consistency in the implementation of daily tasks. creating operational efficiency. Meanwhile, promotions can make employees continue to improve their skills and abilities. The combination of work discipline and promotions creates a positive cycle where employees continually strive to develop. creating a dynamic and progressive work environment.